Encyclopedia of Medical Devices and Instrumentation 2006
DOI: 10.1002/0471732877.emd024
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials: Bioceramics

Abstract: Bioceramics are ceramics that can be used for the reconstruction or regeneration of diseased or damaged tissues, they can be bioinert (e.g., alumina and zirconia), resorbable in the body (e.g., tricalcium phosphate), or bioactive (e.g., bioactive glass, hydroxyapatite), which bond to certain tissues and are used in regenerative medicine. In orthopedics, diseased joints are traditionally replaced by prostheses made of bioinert materials that may last up to 15 years. Advanced metal alloys, special polymers, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Presently, the L929 cell line is widely used to evaluate the cytotoxicity of materials (Torabinejad et al 1995;Kaga et al 2001;Serrano et al 2004;Scharnweber et al 2008) based on the requirement of ISO 10993 (International Standards Organization 10993 1992). Testing by this standard, 45S5 Bioglass has been widely reported to possess excellent biocompatibility (Shirtliff & Hench 2003;Wilson et al 2004;Jones & Hench 2006). As confirmed in this work, MTT result showed that the RGR of L929 cells was significantly more than 100 per cent, thus the corresponding cytotoxicity type was class 0, indicating no cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, the L929 cell line is widely used to evaluate the cytotoxicity of materials (Torabinejad et al 1995;Kaga et al 2001;Serrano et al 2004;Scharnweber et al 2008) based on the requirement of ISO 10993 (International Standards Organization 10993 1992). Testing by this standard, 45S5 Bioglass has been widely reported to possess excellent biocompatibility (Shirtliff & Hench 2003;Wilson et al 2004;Jones & Hench 2006). As confirmed in this work, MTT result showed that the RGR of L929 cells was significantly more than 100 per cent, thus the corresponding cytotoxicity type was class 0, indicating no cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…fabricated bioactive glass nanoparticle-loaded chitosan–gelatin hydrogel beads [ 94 ]. The phosphate and calcium component of bioactive glasses could be converted to hydroxyapatite to stimulate osteogenic differentiation through different pathways [ 95 ]. The ions from the bioactive glass in a nanocomposite form activated the osteoblast genotype expression of dental pulp stem cells by upregulation of ALP activity in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, incorporation of bioactive fillers to hydrogels have shown an increase in bioactivity like the ability to drive differentiation processes. In this way, bioactive glass (BG), a bioceramic formed by threedimensional network of SiO 2 , in which a silicon atom (Si) coordinated with four oxygen atoms (O), and phosphate (P) and calcium (Ca) can stimulate osteogenic differentiation through different pathways [15]. BG also provides a topography that allows cell adhesion; its surface is converted to hydroxyapatite, and its dissolution products (ions) can induce signaling pathways that promote the production of the bone-like extracellular matrix, angiogenic factors, and mediators of inflammation [16,17].…”
Section: Introductionmentioning
confidence: 99%